2022
DOI: 10.3389/fimmu.2021.791278
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Management of Ocular Ischemia in Takayasu’s Arteritis: A Case-Based Systematic Review

Abstract: BackgroundTakayasu’s arteritis (TA) is a rare, chronic granulomatous large-vessel vasculitis that can lead to ocular ischemia. Ocular outcomes after therapeutic management in TA remain largely unknown. We herein conduct a case-based systematic review to address the current treatment options in this particular cohort.MethodsPubMed, Medline, and EMBASE databases were searched pertaining to ocular outcomes after systemic treatment in TA. Studies reporting ocular examinations before and after treatment in TA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…This combination is consistent with the 2018 EULAR recommendations for the management of large vessel vasculitis [119]. Zeng et al also proposed a similar algorithm to cope with ocular ischemia in the course of TA [113]. Moreover, their systematic review suggested surgical intervention in conjunction with medications in order to achieve the best results.…”
Section: Discussionsupporting
confidence: 72%
“…This combination is consistent with the 2018 EULAR recommendations for the management of large vessel vasculitis [119]. Zeng et al also proposed a similar algorithm to cope with ocular ischemia in the course of TA [113]. Moreover, their systematic review suggested surgical intervention in conjunction with medications in order to achieve the best results.…”
Section: Discussionsupporting
confidence: 72%
“…4 shows the representative FFA image of the eye with TR. [ 67 ]
Figure 4 Representative FFA. LE showing (a) patchy choroidal filling and a prolonged arm-to-retina circulation time, (b) Leading edge of fluorescein dye in the arteries, (c) Multiple MAs in the mid-peripheral retina, (d) Diffuse dye leakage in the late phase with mildly dilated retinal veins.
…”
Section: Discussionmentioning
confidence: 99%
“…Small vessels could also be the direct target of the disease, as assumed by Das et al [ 21 ]. Possible autoimmune processes, including immune-regulatory genes and inflammatory cytokines involved in TA, could also play a role in the initial pathogenic stimulus targeted to molecules or subcellular elements of zonular components.…”
Section: Discussionmentioning
confidence: 99%